1980
DOI: 10.2190/vp4l-94kx-491m-1wve
|View full text |Cite
|
Sign up to set email alerts
|

Weathering Widowhood: Problems and Adjustment of the Widowed during the First Year

Abstract: Widows (n = 78) and widowers (n = 41) whose spouses died at a midwest suburban hospital were interviewed thirteen to sixteen months after they were widowed. An 8–item self-report measure of adjustment-depression was developed. The article discusses the factors related to adjustment, the problems faced by the widowed during the first year of bereavement, those who helped the most during the final hospitalization and during bereavement, and finally some practical considerations for those who are concerned with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 4 publications
5
26
2
Order By: Relevance
“…(33) Widowed women also had higher odds of MDD than their single counterparts, as the death of a spouse may have adversely affected their mental health. (34) Contrary to some findings that marriage was a 'buffer' or protective factor for depression, (3,35) others have found that married women were more likely to have higher rates of depression compared to those who were divorced or separated; (36) however, we did not find this association among our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…(33) Widowed women also had higher odds of MDD than their single counterparts, as the death of a spouse may have adversely affected their mental health. (34) Contrary to some findings that marriage was a 'buffer' or protective factor for depression, (3,35) others have found that married women were more likely to have higher rates of depression compared to those who were divorced or separated; (36) however, we did not find this association among our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, older widows and widowers had worse outcomes than younger widowed individuals. Although some studies suggest a relationship in the opposite direction (Sable, 1991) or a non-linear connection (Fitzpatrick and Van Tran, 2002), this outcome is consistent with most preceding studies reporting an association between age and distress (Carey, 1979;Cotten, 1999;Mendes de Leon et al, 1994). The impact of education on bereavement outcome has been less examined.…”
Section: Discussionsupporting
confidence: 90%
“…Not all studies manage to demonstrate a relationship between education and psychological adjustment (Feinson, 1982). However, where an association was found, it was in the same direction as demonstrated in our study (Carey, 1979). Poorly educated widows and widowers experienced more distress.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations